Formulation and Evaluation of Solid Lipid Nanoparticle (SLN) Based Topical Gel of Etoricoxib - Roohi Kesharwani, Anupam Sachan, Swati Singh, Dilip Patel (Journal of Applied Pharmaceutical Science, 2016)
The objective of present investigation was to prepare & evaluate solid lipid nanoparticle (SLN) based topical gel of non- steroidal anti-inflammatory drug (NSAID) etoricoxib for the treatment of arthritis which would attenuate the gastrointestinal related toxicities associated with oral administration. SLN were formulated by melt emulsification and solidification at low temperature method using stearic acid & tween 80. All the formulation were subjected to particle size, particle size distribution, zeta potential, scanning electron microscopy, crystallinity study by DSC and in-vitro release studies. It has been observed that, the high lipid concentration containing formulation have higher entrapment as compare to other two formulation. The SLN- dispersion shows 70.766% entrapment & zeta potential of the formulation were -25.6 which indicates the stability of formulation. The In Vitro drug release rate of gel was evaluated using Modified franz diffusion cell containing dialysis membrane with phosphate buffer pH 7.4 as the receptor medium. The in-vitro release was carried out in comparison with a carbopol gel & hydroxypropylmethylcellulose (HPMC) gel. The permeability parameters steady-state flux (Jss) was significantly increased in SLN-F3C (carbopol) formulation as compared with SLN-F3HPMC (hydroxypropyl methylcellulose) formulation. It was concluded that the Etoricoxib loaded SLN based gel formulation containing carbopol was suitable for topical application and shows much better result of anti-inflammatory activity.
Keywords: Etoricoxib, solid lipid nanoparticle (SLN), topical gel, diffusion cell.